2013
DOI: 10.1371/journal.pone.0080856
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Diabetic Foot and Leg Ulcers in a Developing Country with a Rapid Increase in the Prevalence of Diabetes Mellitus

Abstract: ObjectiveTo identify the socio demographic, life style and foot examination related predictors of diabetic foot and leg ulcers with a view to develop a screening tool appropriate for the use in an outpatient setting.Research design and methodsThis cross sectional study included type 2 diabetes mellitus (DM) patients; 88 subjects with leg and foot ulcers and 80 non ulcer controls. Socio demographic data and life style factors were documented. Foot was examined for skin changes and structural abnormalities. Dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 31 publications
5
36
0
4
Order By: Relevance
“…[8][9][10] The foot problems are observed in 25 cases (40.66 %) having DM for the duration of 5-10 years which in accordance with findings reported by Singh and Chawla. [10,11] The 90% (54 out 60 ) of cases of type II diabetes had developed foot infections which is comparable with finding which is comparable with the reviewed literature. The present study revealed 43.33 % infections are caused by gram positive organisms, Staphylococcus aureus and Streptococcus whereas Aamir et al from Pakistan reported 46 % of DFI caused by staphylococcus aureus.…”
Section: Discussionsupporting
confidence: 86%
“…[8][9][10] The foot problems are observed in 25 cases (40.66 %) having DM for the duration of 5-10 years which in accordance with findings reported by Singh and Chawla. [10,11] The 90% (54 out 60 ) of cases of type II diabetes had developed foot infections which is comparable with finding which is comparable with the reviewed literature. The present study revealed 43.33 % infections are caused by gram positive organisms, Staphylococcus aureus and Streptococcus whereas Aamir et al from Pakistan reported 46 % of DFI caused by staphylococcus aureus.…”
Section: Discussionsupporting
confidence: 86%
“…Certain practices such as barefoot walking are common in rural areas in South Asia [88] and contribute greatly to foot ulcerations [89] Unsafe foot wear practices were seen in 46.9% of 300 people with T2DM in Mumbai, India [90]. Wearing covered shoes was protective against development of ulcers in a study in 168 patients with DM in Sri Lanka (OR 0.003) [91] In a cross sectional study in seven states across India, 56.4% of the population in the urban area and 46.6% of the population in the rural area had knowledge of foot care in diabetes [92]. On the other hand, only 6% of patients with diabetes practised proper foot care in Islamabad, Pakistan [93].…”
Section: Diabetic Footmentioning
confidence: 99%
“…Howell-Jones and colleagues10 evaluated findings from 95 microbiology laboratories; they found that 41% of swabs from venous leg ulcers were associated with an unpleasant odor. Foot ulcers occur in approximately 15% of persons with diabetes mellitus 11. Diabetes mellitus, symptomatic bacterial wound infection, vascular diseases, and necrosis of tissues may trigger and prolong inflammation,8–11 thus impeding the healing process; these sequelae increases the risk for development of wound malodor 1115…”
Section: Introductionmentioning
confidence: 99%